Utilization of tanniniferous feeds: 5. Effect of supplementation of Acacia nilotica pods on productive performances of crossbred cows - BARMAN, K; RAI, S N (The Indian Journal of Animal Sciences, 2011)
Crossbred lactating cows (15) were divided into 3 groups of 5 animals each in randomized block design on the basis of milk yield, fat% and body weight, and supplemented with concentrate mixture containing 0, 20 and 40% Acacia pods as a source of tannin to study its effect on productive performance of cows. Dry matter (DM) intake (kg/d) was decreased with increased level of pods in the diet. However, DM intake (kg/lOOkg body weight) was found similar across all supplemental level of Acacia pods. Dry matter intake (kg/kg milk yield) was increased at 20% supplemental level of pods, but found similar at 0 and 40% level of supplementation. Milk yield was reduced at both 20 and 40% supplemental levels of Acacia pods in the concentrate mixture. It is concluded that the dry matter intake is reduced and protein content of milk is increased with increased levels of pods in the diet. Acacia pods may be supplemented up to 20% level in the concentrate mixture of lactating crossbred cows.Â